Validity and Reliability of MoCA-Ina for Assessing Cognitive Function in Dialysis Patients with Chronic Kidney Disease - Sagala, Ida Meita; Rifai, Achmad; Satiti, Ika Ayu Dewi; Setyabudhi, Verina (Universitas Brawijaya, 2025)
BACKGROUND: Montreal Cognitive Assessment (MoCA) is widely used for assessing cognitive function in chronic kidney disease (CKD) patients, but its effectiveness in Indonesian CKD populations remains unclear compared to studies in other regions. OBJECTIVES: To evaluate the reliability and validity of the translated MoCA in assessing cognitive impairment among dialysis patients. METHODS: This cross-sectional study was conducted at the hemodialysis and Continuous Ambulatory Peritoneal Dialysis (CAPD) unit of RSUD Dr. Saiful Anwar in Indonesia from January to February 2024. The study utilized the Indonesian Version of MoCA for cognitive assessment. Reliability and validity of the questionnaire were evaluated using Cronbach's Alpha and Pearson validity test methods. RESULTS: In this study, 43 participants were enrolled, including 21 undergoing hemodialysis and 22 receiving CAPD. MoCA's reliability was confirmed with Cronbach's Alpha values of 0.648 for hemodialysis and 0.737 for CAPD, indicating strong internal consistency. The questionnaire exhibited favorable discriminatory power, with corrected item-total correlation scores exceeding 0.3 for all items in both groups. Validity demonstrated strong construct validity, with critical values surpassing standard references. All statistical significance levels were below 0.05, affirming MoCA's reliability in assessing cognitive function in dialysis patients. CONCLUSION: In conclusion, our study has demonstrated that the translated MoCA is valid and reliable for assessing cognitive function in CKD patients undergoing dialysis.